Prolotherapy Improves Anatomical and Clinical Outcomes in Monosodium Iodoacetate Induced Model of Osteoarthritis - Zahid, Aqsa; Qamar, Khadija; Qamar, Abdullah; Faisal, Tayyaba; Iftikhar, Zubia; Saleem, Saba (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the ameliorative effects of Prolotherapy on the pain score of the gait cycle in Monosodium Iodoacetate (MIA) induced osteoarthritis in the rat knee joint. Study Design: Laboratory-based experimental study. Place and Duration of Study: Department of Anatomy, Army Medical College, Rawalpindi in collaboration with the National Institute of Health (NIH), Islamabad and Pathology Lab Pak Emirates Rawalpindi, Pakistan, from Aug to Nov 2021. Methodology: Thirty male Sprague Dawley rats were randomly divided into three groups (n=10 in each group). The control group was Group-A. To induce osteoarthritic changes in Group-B, a single dose of 1mg Monosodium Iodoacetate was injected intra-articularly into the right knee. Group-C received a single dose of 1mg Monosodium Iodoacetate injection in the right knee intra articularly to induce osteoarthritic changes, and was followed by 0.1ml Prolotherapy (3ml of 25% dextrose, 2ml of 2% Xylocaine, 1ml of injection thiamine, and 1ml of injection Methylcobalamin) at 2, 6 and 10 weeks intra articularly into the right knee joint. Before euthanasia, Pain scoring schemes for gait in rats of all groups were done at 0, 2 and 14 weeks. Results: The present study concluded that prolotherapy improved the gait cycle pain score in experimental group C (p-value 0.001 on the intergroup comparison at two weeks and 14 weeks while p-value 0.001 when compared pain score within the Group C at 0, 2 and 14 weeks). Conclusion: Prolotherapy had ameliorative effects on the pain score of the gait cycle in experimental Group C on Monosodium Iodoacetate......